A review of anaerobic membrane bioreactors (AnMBR) for the treatment of highly contaminated landfill leachate and biogas production: Effectiveness, limitations and future perspectives. (10th May 2020) - Abuabdou, Salahaldin M.A.; Ahmad, Waseem; Aun, Ng Choon; Bashir, Mohammed J.K.
Abstract: Most of the municipal solid wastes (MSW) produced daily in the world are being buried in landfilling sites without any prior treatment particularly in developing countries. These landfills yield leachate which is a highly contaminated wastewater. Thus, a proper treatment of leachate is highly recommended before the final discharge. Recently, the use of membrane separation technology alongside bioreactors have opened a new gateway in treating refractory wastewater such as landfill leachate. Anaerobic membrane bioreactor (AnMBR) is a promising technique for leachate treatment due its substantial benefits over other conventional anaerobic and aerobic technologies. Thus, this study provides a comprehensive review and assessment on the potential practice of AnMBR in treating landfill leachate and its technological advancements in the recent past. A critical review on the performance of a lab-scale AnMBR on landfill leachate with the biogas production is also included in the current work. Moreover, this study inspects various factors affecting the performance of AnMBR along with its limitations and future perspectives. The simultaneous treatment of landfill leachate anaerobically to produce bioenergy complies with the principles of circular economy and sustainable growth. Graphical abstract: Image 1075 Highlights: An overview of AnMBR using municipal landfill's leachate and its biogas production. Waste-to-Energy (WTE) can help to achieve the principles of circular economy. Membrane fouling is one of the major obstacles limiting the application of AnMBR. Identifying research gaps of AnMBR systems and its energy perspectives.